DEVELOPMENT OF A PROTOTYPE FOR THE REDESIGN OF A SIGNATURE LEATHER BAG FEATURING TRADITIONAL INDONESIAN MOTIFS USING THE AESTHETIC FOLLOW FUNCTION (AFF) APPROACH - Moh. Rusnoto Susanto; Mita Purbasari Wahidiyat; Lusiana Lusiana; Bayu Rahmat Setiadi; Zainul Faizien Haza; Nurcholish Arifin Handoyono (International Journal of Multidisciplinary Research and Literature, 2026)
The transformation of the creative industry demands the development of products that are not only functional but also possess a cultural identity and aesthetic value capable of enhancing competitiveness in the market. This study aims to develop a prototype of a redesigned leather bag—a flagship product of CV Quwalli Leather by integrating traditional Indonesian songket woven fabric using an “aesthetic follows function” approach. The methodology employed is Research and Development (R&D) with a Practice-Based Research (PBR) approach, which positions design practice as the primary instrument for knowledge creation. The research stages include material exploration and analysis of existing products, concept and design development, prototype production, as well as prototype testing and evaluation. The results indicate that songket possesses strong visual and symbolic value; however, structural limitations mean this material is better suited as a semi-structural element, while leather serves as the primary structure ensuring the product’s strength and durability. The design process resulted in a hybrid model that integrates function, structural aesthetics, and cultural identity in a cohesive manner. Ergonomic and durability testing showed that load distribution remains optimal and the product’s form stability can be maintained through a lamination system and material reinforcement. User evaluations indicate that the incorporation of songket enhances perceptions of the product’s exclusivity, uniqueness, and cultural value. The research findings confirm that the “aesthetic follows function” approach is effective in integrating cultural heritage into contemporary product design without compromising functionality and performance. The resulting prototypes serve not only as craft-based fashion products but also as a medium for cultural representation capable of enhancing added value, product differentiation, and the competitiveness of the culture-based creative industry in the global market.